Cardiac “hypertrophy” phenotyping: differentiating aetiologies with increased left ventricular wall thickness on echocardiography - Ferkh, Aaisha; Tjahjadi, Catherina; Stefani, Luke; Geenty, Paul; Byth, Karen; De Silva, Kasun; Boyd, Anita C.; Richards, David; Mollee, Peter; Korczyk, Dariusz; Taylor, Mark S.; Kwok, Fiona; et al. (Frontiers in Cardiovascular Medicine, 2023)
Aims: Differentiating phenotypes of cardiac ‘hypertrophy’ with increased wall thickness on echocardiography is essential for management and prognostication. Transthoracic echocardiography is the commonest screening test performed. We sought to identify echocardiographic markers that distinguish infiltrative and stroge disorders that present with increased left ventricular (LV) wall thickness, namely Cardiac Amyloidosis (CA) and Anderson-Fabry (AFD) from hypertensive (HHT) heart disease. Methods: Patients were recruited retrospectively from Westmead Hospital, Sydney and Princess Alexandra Hospital, Brisbane. LV structural, systolic and diastolic function parameters, global (LVGLS) and segmental longitudinal strain were assessed. Previously reported echocardiographic parameters including relative apical sparing (RAS), LV ejection-fraction to strain ratio (EFSR), mass-to-strain ratio (MSR) and AMYLI score (relative wall-thickness x E/e’) were evaluated. Results: 209 patients (120 CA (58 ATTR, 62 AL), 31 AFD and 58 HHT patients; mean age 64.1±13.7yrs, 75% male) comprised the study cohort. Echocardiographic measurements differed across the three groups; Indexed LV-mass was higher in both CA (median 126.6 IQR 106.4-157.9 g/m2) and AFD (median 134 (IQR 108.8-152.2 g/m2) versus HHT (median 92.7 (IQR 79.6-102.3 g/m2, p<0.05). LVGLS was lowest in CA (median 12.29 IQR 10.33-15.56%) followed by AFD (median 16.92 IQR 14.14-18.78%) then HHT (median 18.56 IQR 17.51-19.97%, p<0.05). Diastolic function measurements including average-e’ and E/e’ were most-impaired in CA and least-impaired in AFD. Indexed left atrial volume was highest in CA. EFSR and MSR differentiated secondary (CA+AFD) from HHT (receiver operating curve-area under curve (ROC-AUC) of 0.80 and 0.91 respectively). RAS and AMYLI score differentiated CA from AFD (ROC-AUC of 0.79 and 0.80 respectively). Linear discriminant analysis with stepwise variable selection using linear combinations of indexed LV-mass, average-e’, LVGLS, and basal strain correctly classified 79% of all cases. Conclusion: Simple echocardiographic parameters differentiate between ‘hypertrophic’ cardiac phenotypes. These have potential utility as a screening tool to guide further confirmatory testing.